2018
DOI: 10.7759/cureus.3458
|View full text |Cite
|
Sign up to set email alerts
|

Low Socioeconomic Status Leading to Unsafe Abortion-related Complications: A Third-world Country Dilemma

Abstract: IntroductionAn unsafe abortion is a persistent, preventable dilemma. It is a procedure where an unintended pregnancy is terminated either by untrained individuals, or in an environment not meeting medical standards, or both, as defined by the World Health Organization (WHO). It endangers women in developing countries, where abortion is restricted either by law and culture or legally permitted but not easily accessible. Induced abortions are usually performed by unqualified and untrained individuals or are self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…[23] On the other hand, maternal morbidity is an inequality and discrimination in woman's human right: the right to life and survival; there is a dire need to prevent these unpleasant morbidities by improving the quality of care such as providing safe abortion services. [24] In addition, to provide quality services, the maternal morbidity-avoidable factors in hospitals should be identified and understood better, which can be cited for emergency obstetric causes such as preeclampsia, eclampsia, hemorrhage, sepsis, and thromboembolism. [2526]…”
Section: Resultsmentioning
confidence: 99%
“…[23] On the other hand, maternal morbidity is an inequality and discrimination in woman's human right: the right to life and survival; there is a dire need to prevent these unpleasant morbidities by improving the quality of care such as providing safe abortion services. [24] In addition, to provide quality services, the maternal morbidity-avoidable factors in hospitals should be identified and understood better, which can be cited for emergency obstetric causes such as preeclampsia, eclampsia, hemorrhage, sepsis, and thromboembolism. [2526]…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, a study from Ghana showed that about 60% of women under 25 years were more likely to have unsafe abortion [12] and in other parts of Africa [13]. Similarly, other studies have found that unmarried, lower education level and poverty are predictors of unsafe abortion [10, 12, 14, 15]. Also, some pregnancy-related factors such as being unaware that abortion is free, unwanted pregnancy, unmet need for modern contraceptive methods, and being unaware that abortion is legal have contributed to inequalities in unsafe abortion [16-19].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 17 million abortions that take place in LMICs are deemed unsafe (Alkema et al, 2016). Many of these unsafe abortions are either performed by unqualified and untrained individuals or are self-induced by the women themselves (Zafar, Ameer, Fiaz, Aleem, & Abid, 2018), with the highest incidence reported in sub-Saharan Africa where unsafe abortion occurs at rates of 18-39 per 1,000 women (Rasch, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Post-abortion, these women typically delay in seeking care, further increasing the risk of complications including bleeding, infection and uterine rupture. Evidence in the literature shows that these complications constitute a major burden of disease and contribute to prolonged hospitalisation as well as an increase in the cost of care (Zafar et al, 2018). Evidence also suggests that the direct costs of treating complications of abortion is a huge burden for LMICs and its indirect costs are catastrophic for families and communities (Grimes et al, 2006).…”
Section: Introductionmentioning
confidence: 99%